Perempuan dalam Tayangan Iklan di Televisi - Kurniadi, Oji (Mediator, 2007)
As part of marketing activities, advertising played a very important role. Through the means of advertising, a product with all its characteristics and qualities was being introduced to the public. The ad creators competitively search ideas to construct an attractive ad. The depiction of women becomes one of the old-but-believed-to-be-effective-formula for such advertisings. In the world of advertising and marketing, women are not only becoming models for women products, but also for men products. Women figures were depicted beside men models in cigarettes advertising and in turn seemed problematic. A strong and unending debate has been circulating amongst public concerning advertising who significantly exploited women’s sensuality. These kinds of ads are believed degraded women and create negative image for women.